Second Instagram accounts: A study of Generation Z's Self-Identity in Medan - Ahmad Gifari Alamsyah; Ayeisha Ardelisma; Andhika Nugraha; Miftahul Jannah (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2025)
This study investigates the role of secondary Instagram accounts in the self-identity representation of Generation Z in Medan City, employing a qualitative phenomenological approach based on Erving Goffman's dramaturgical theory. The primary aim of this research is to elucidate how Generation Z articulates their self-identity through secondary Instagram accounts. Data were collected through observations, interviews, and documentation, and data analysis encompassed reduction, presentation, and conclusion formulation. The findings indicate that the utilization of a secondary Instagram account signifies an effort to delineate private and public life within the digital sphere, thereby affording individuals the opportunity to express themselves more authentically and unencumbered by societal expectations. However, the maintenance of dual accounts also poses challenges, such as difficulties in managing time and energy and potential privacy infringements. From the perspective of dramaturgical theory, the primary account serves as a front stage that adheres to social norms, whereas the secondary account functions as a more liberated backstage. The novelty of this research lies in its examination of the phenomenon of secondary account usage among Generation Z Indonesians, a topic that remains underexplored in the existing literature. The implications of this study for future research include further investigation into the impact of dual-account usage on digital identity formation and social interaction. Practically, the findings of this study can offer insights for social media developers and digital communication practitioners regarding the dynamics of self-identity within the context of social media, while also enriching the theoretical understanding of digital identity through dramaturgical theory.   Penelitian ini mengkaji peran second account Instagram dalam representasi identitas diri Generasi Z di Kota Medan dengan menggunakan pendekatan kualitatif fenomenologi yang berlandaskan pada teori dramaturgi Erving Goffman. Tujuan utama penelitian ini adalah untuk memahami bagaimana Generasi Z mempresentasikan identitas diri mereka melalui akun kedua di Instagram. Pengumpulan data dilakukan melalui observasi, wawancara, dan dokumentasi, sementara analisis data melibatkan reduksi, penyajian, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa penggunaan second account Instagram mencerminkan upaya untuk memisahkan kehidupan pribadi dan publik dalam ranah digital, memberikan ruang bagi individu untuk mengekspresikan diri secara lebih autentik dan bebas dari ekspektasi sosial. Meskipun demikian, penggunaan dua akun ini juga menghadirkan tantangan, seperti kesulitan dalam pengelolaan waktu dan energi serta potensi pelanggaran privasi. Berdasarkan perspektif teori dramaturgi, akun utama berfungsi sebagai panggung depan yang beroperasi sesuai dengan norma sosial, sedangkan second account berfungsi sebagai panggung belakang yang lebih bebas. Kebaruan dari penelitian ini terletak pada kajian fenomena penggunaan second account di kalangan Generasi Z Indonesia yang masih terbatas dalam literatur yang ada. Implikasi penelitian ini untuk penelitian selanjutnya mencakup eksplorasi lebih lanjut tentang dampak penggunaan dua akun terhadap pembentukan identitas digital dan interaksi sosial. Secara praktis, hasil penelitian ini dapat memberikan wawasan bagi pengembang media sosial serta praktisi komunikasi digital mengenai dinamika identitas diri dalam konteks media sosial, sekaligus memperkaya pemahaman teoritis tentang identitas digital melalui lensa teori dramaturgi.